Emerging Directions in CAR-T Cell Therapy: Solid Tumors - Magiera, Michał; Sikora, Miłosz; Czwałga, Piotr; Koprowska, Patrycja (Quality in Sport, 2026)
Background. CAR-T therapy represents a breakthrough in immuno-oncology, enabling tumor elimination independently of the MHC system. This strategy has achieved spectacular clinical success in hematology (ALL, DLBCL), primarily by targeting CD19 and BCMA antigens. However, adapting this technology to solid tumors, which account for approximately 90% of cancer cases, remains a challenge. Given the rising incidence in an aging population, overcoming the barriers limiting CAR-T efficacy in this group has become a critical research priority. Aim. The aim of the study was to summarize the current state of knowledge, challenges and emerging strategies for the use of CAR-T therapy in the treatment of solid tumors, based on the latest literature reports. Materials and methods. A literature review was conducted using PubMed, Google Scholar, and Web of Science databases, focusing primarily on articles published between 2023 and 2025, alongside relevant historical context. The search utilized the following keywords: CAR-T cells, immunotherapy, tumor microenvironment, breast cancer, lung cancer, and solid tumor. The analysis included only English-language publications. Results. The analysis tracks CAR evolution from 1st to 5th generation, emphasizing costimulation and TRUCK systems. In solid tumors (e.g., TNBC, NSCLC), efficacy is hindered by the immunosuppressive microenvironment (TME), antigen heterogeneity, and physical barriers. Key strategies to overcome these include combination with checkpoint inhibitors, CRISPR/Cas9 editing, Dual-CAR systems, and cytokine induction. Conclusions. CAR-T technology extends beyond hematology, showing promising potential in solid tumors, autoimmune diseases, and neurodegenerative disorders. New modification strategies overcome microenvironmental barriers in solid tumors, while CAR-T and CAR-Tregs effectively restore immune homeostasis in autoimmunity. This therapy is evolving into a versatile platform with broad translational significance.